The effect of an anti-inflammatory diet on chronic pain: a pilot study - Sala-Climent, Marta; López de Coca, Teresa; Guerrero, María Dolores; Muñoz, Francisco Javier; López-Ruíz, María Amparo; Moreno, Lucrecia; Alacreu, Mónica; Dea-Ayuela, María Auxiliadora (Frontiers in Nutrition, 2023)
Objective: Rheumatic diseases result in chronic pain (CP) and require treatment with drugs whose prolonged administration is associated with side effects. However, publications in the academic literature have suggested that diet modification and food supplementation can play a crucial role in alleviating the symptoms of inflammatory disease. Thus, it is hoped that the use of an anti-inflammatory diet for pain management might result in improved quality of life. Hence, here we aimed to investigate the effect of anti-inflammatory foods in patients with CP caused by rheumatic diseases. Methods: After an exhaustive bibliography search, we designed a 13-item anti-inflammatory dietary guide based on a Mediterranean diet without red meat, gluten, or cow’s milk (the AnMeD-S). We then conducted a pilot study to evaluate the efficacy of this anti-inflammatory diet in patients with CP. A food consumption score (with a maximum of 156 points) was then applied to evaluate patient adhesion to the proposed diet. Forty-five patients with CP were followed-up for four months. Variables related with quality of life (including pain perception, depression status, and sleep satisfaction) were measured using 9 validated questionnaires and anthropometric measurements were recorded before and after the participants followed the anti-inflammatory diet. Results: We found a correlation between increased anti-inflammatory food intake and improved physical characteristics, stress, and pain in the patients we assessed. Moreover, decreased consumption of pro-inflammatory foods was positively correlated with sleep satisfaction. Following the AnMeD-S was associated with improved physical characteristics and quality-of-life in patients with CP. Conclusions: The AnMeD-S, includes anti-inflammatory foods and restricts the consumption of certain pro-inflammatory foods (such as those containing gluten). This dietary pattern could provide relief from CP and improve the symptoms of stress and depression, as well as reducing sleep disturbances.